2015
DOI: 10.17265/2162-5263/2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mineral Nutrients for Biomass Production by Young Birch Stands and Stands Vitality in Different Forest Growing Conditions

Abstract: Abstract:The data of field studies about mineral nutrient content in the biomass components of young birch stands (9-15 years old) in different forest growing conditions and soil types have been analyzed. In forest growing conditions on fertile soils (ASG, TSC and SP) the total amount of biomass produced by young birch stands divides into fractions as follows: stem wood 51.8%-59.5%; branch wood 9.8%-12.4%; foliage 5.7%-6.8%; stump wood and roots 25%-30%. In forest types on lean soils (TP) the same indices are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Additionally, Uri et al (2012) and Gawęda et al (2014) observed increasing contents of the major nutrients in soils under birch chronosequences. Birch biomass is generally moderately abundant in nutrients; however, their concentrations are strongly controlled by their bioavailability (Daugaviete et al 2015). Nutrient distribution is uneven in tree organs, usually reaching their highest contents in the leaves, followed by the fine roots or bark, with the lowest in the stemwood (Rustowska 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Uri et al (2012) and Gawęda et al (2014) observed increasing contents of the major nutrients in soils under birch chronosequences. Birch biomass is generally moderately abundant in nutrients; however, their concentrations are strongly controlled by their bioavailability (Daugaviete et al 2015). Nutrient distribution is uneven in tree organs, usually reaching their highest contents in the leaves, followed by the fine roots or bark, with the lowest in the stemwood (Rustowska 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Проблема лесоразведения очень остро стоит в Прибалтийский странах на бывших сельскохозяйственных землях. Достаточно много исследований роста и развития березовых лесов проводится в Финляндии и Швеции [1][2][3][4][5].…”
Section: Introductionunclassified
“…Additionally, Uri et al (2012) and Gawęda et al (2014) observed increasing contents of the major nutrients in soils under birch chronosequences. Birch biomass is generally moderately abundant in nutrients; however, their concentrations are strongly controlled by their bioavailability (Daugaviete et al 2015). Nutrient distribution is uneven in tree organs, usually reaching their highest contents in the leaves, followed by the ne roots or bark, with the lowest in the stemwood (Rustowska 2022).…”
Section: Introductionmentioning
confidence: 99%